HJIIR MENTUK : POTENSI KULINER LOKAL OLAHAN MASYARAKAT KAMPUNG TOBATI SEBAGAI DAYA TARIK WISATA DI KOTA JAYAPURA - Ilham Ilham; Simon K. Abdi Frank; Marlina Flassy; M. Zaenul Muttaqin; Usman Idris; Dian Indri Yunita (Jurnal Pariwisata Pesona, 2021)
The study was conducted as an effort to raise the potential of local culinary hjiir mentuk as a tourist attraction. The location of the research was carried out in Tobati Village through a qualitative approach and literature. Data was collected through observation, interviews, documentation and literature searches. Furthermore, data analysis was carried out through reduction, data presentation and drawing conclusions. The results of this study indicate that Tobati Village is known for cultural tourism, especially the art of relief, dance and singing including its culinary arts so that it can be developed as a tourist village. Culinary as one of the sub-sectors of the creative industry has great potential as a tourist attraction, such as; Processed papeda made from sago with yellow sauce. This culinary can be juxtaposed with the dessert hjiir mentuk from Tobati Village which is part of the travel experience. The local culinary potential can be developed through promotional activities by implementing the DOT BAS and POSE strategies; Destination, Origin, and Time [DOT], Branding, Advertising, and Selling [BAS] and Paid Media, Own Media, and Social Media [POSE]. This promotional activity can be carried out jointly through synergy between the government, tourism industry players and the community. Through promotional activities, it can increase tourist visits which stem from improving the quality of life of the community.